2018
DOI: 10.1016/j.jmii.2016.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features, antifungal susceptibility, and outcome of Candida guilliermondii fungemia: An experience in a tertiary hospital in mid-Taiwan

Abstract: Despite the lower mortality rate associated with C. guilliermondii fungemia, the removal of a central venous catheter remained an independent factor influencing the outcome of patients. The clinical significance of less susceptibility of C. guilliermondii to triazoles and echinocandins remains to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 35 publications
1
12
1
Order By: Relevance
“…The mean age of patients in our study was older than the mean ages in previous studies, possibly because we mainly focused on critically ill patients; critically ill patients are often older than other patients [2, 19, 20]. Similar to other studies, C. albicans was the most common species causing candidemia, followed by C. parapsilosis, C. glabrata, and C. tropicalis [2125].…”
Section: Discussionsupporting
confidence: 53%
“…The mean age of patients in our study was older than the mean ages in previous studies, possibly because we mainly focused on critically ill patients; critically ill patients are often older than other patients [2, 19, 20]. Similar to other studies, C. albicans was the most common species causing candidemia, followed by C. parapsilosis, C. glabrata, and C. tropicalis [2125].…”
Section: Discussionsupporting
confidence: 53%
“…M. guilliermondii is rarely recognized as an invasive pathogen, it is part of the normal microbiota of the skin and mucosa. Infections caused by this species are particularly common in immunocompromised people (Clancy and Calderone, 2012;Tseng et al, 2017). C. parapsilosis was one of the most common white yeasts in our samples.…”
Section: Discussionmentioning
confidence: 72%
“…e test range was as follows: FCZ, 0.125 to 64 mg/L; VCZ, 8 mg/L; and ICZ, 8 mg/L (European Society of Clinical Microbiology and Infectious Diseases, 2020). MIC values were interpreted according to EUCAST 2020 and CLSI M27 (Clinical and Laboratory Standards Institute, 2017; European Society of Clinical Microbiology and Infectious Diseases, 2020; Tseng et al, 2018). EUCAST 2020 did not provide any breakpoints for M. guilliermondii; therefore, based on Tseng et al (2018), we determined the epidemiological cutoff values for non-wild isolates (resistant) as >8, >0.5, and >1 mg/L for FCZ, VCZ, and ICZ, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Some authors have indicated that M. guilliermondii as a re-emerging pathogen, especially in patients with cancer. e documented cases of infection indicate a mortality rate of up to 66% (Ahangarkani et al, 2019;Castillo-Bejarano et al, 2020;Tseng et al, 2018). In M. guilliermondii, cross-resistance between MTX and FCZ has never been observed before.…”
Section: Candida Guilliermondii)mentioning
confidence: 99%